Supraphysiological Levels of IL-2 in Jak3-Deficient Mice Promote Strong Proliferative Responses of Adoptively Transferred Naive CD8+ T Cells - Lee, Gil-Woo; Lee, Sung-Woo; Kim, Juhee; Ju, Young-Jun; Kim, Hee-Ok; Yun, Cheol-Heui; Cho, Jae-Ho (Frontiers in Immunology, 2021)
The antigen-independent, strong proliferative responses of naive CD8+ T cells have been well demonstrated in a particular strain of mice lacking IL-2 receptors. This type of proliferation is mainly driven by common gamma-chain (gc) cytokines, such as IL-2, IL-7, and IL-15, present at abnormally high levels in these mice. Similarly, in the present study, we showed that mice lacking Janus kinase 3 (Jak3), a tyrosine kinase crucial for c cytokine signaling, could induce strong proliferation of adoptively transferred naive CD8+ T cells. This proliferation was also independent of antigenic stimulation, but heavily dependent on IL-2, as evidenced by the failure of proliferation of adoptively transferred IL-2 receptor alpha- and beta-chain-deficient naive CD8+ T cells. Consistent with this, Jak3-/- mice showed elevated serum levels of IL-2 compared to wild-type mice, and interestingly, IL-2 production was due to high levels of accumulation of activated CD4+ T cells in Jak3-/- mice along with defective CD4+ T regulatory cells. Collectively, these findings reveal previously unidentified unique immune contexts of Jak3-/- mice that cause robust IL-2-driven T cell expansion and have a clinical implication for designing a treatment strategy for human patients with loss-of-function genetic mutations of Jak3.